(3JMaI GdCMHGH aj Yde GdMSGHs - (3eMeO Hf eMeO Hf CMeO GdZRGd GdOeTbqj, HOQ GdOjf, GdTgjQ HSHW GdeGQOjfj , J (B912 (3g` s ((3LGeY GdCRgQ s)
(3ChdgG (B:s
(3GdMeO ddg ejSQ GdMSGH heghf GdUYGH gPG eNJUQ ai Yde GdMSGH efgd def jQjO GdTQhY ai GdaQGFV ef Chdi GdCdHGH s
(3BNQgG (B:s
(3aCVQH dcd efgeG MUJg ai GdeGFI Ch habgG hCbSe GdMGUd Ydi GdEeGe s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B54 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B188s
Keywords: (3GdQjGVjGJs